Chick provisioning and nest attendance of male and female Wilson’s storm petrels Oceanites oceanicus - Gladbach, Anja; Braun, Christina; Nordt, Anja; Peter, Hans-Ulrich; Quillfeldt, Petra (2021)
Seabirds show a range of patterns of sexual size dimorphism and sex-specific parental investment, but the underlying causes remain poorly understood. The aim of the present study was to test two longstanding hypotheses of parental investment in a sexually monomorphic species, Wilson’s storm petrel Oceanites oceanicus, namely that males attend chicks more frequently and females deliver larger meals (Beck and Brown in Br Antarct Surv Sci Rep 69:1–54, 1972). We recorded in eight seasons, both during incubation and chick rearing, which adult was caught first in a nest and found no difference in the probability of catching a male or a female first in any year. Additionally, in five seasons we employed a miniature video camera to record nest attendance during chick rearing and found no significant difference except for 2006, a year with very low krill availability, where females visited the nest less often than males. We then combined video observations with periodic weighing of chicks to estimate mean daily feeding mass (g/day) of males and females and found no difference in the amount of food delivered per day between the sexes. However, in years with low krill availability, males and females tended to use different strategies to achieve the same feeding rates, with females undertaking longer foraging trips and delivering heavier meals. Thus, our results do not support the hypothesis of a general sex-specific parental investment in Wilson’s storm petrels, but a tendency for a context-dependent sex-specific investment in the years of food shortage.